A System-Oriented Dialogue Model to Design Community Partnerships for More Effective Sars-Cov-2 Prevention in Schools: The Case of Spain - Rosina Malagrida; Rosina Malagrida; Jessica Fernández; Jordi Casabona; Jordi Casabona; Jacqueline E. W. Broerse (Frontiers Media S.A., 2023)
Objectives: The European Centre for Disease Control (ECDC) COVID-19 guidelines for non-pharmaceutical interventions (NPI) identify safety, hygiene and physical distancing measures to control SARS-Cov-2 transmission in schools. Because their implementation requires complicated changes, the guidelines also include "accompanying measures" of risk communication, health literacy and community engagement. Although these are considered crucial, their implementation is complex. This study aimed to co-define a community partnership that a) identifies systemic barriers and b) designs recommendations on how to implement the NPI to improve SARS-Cov-2 prevention in schools.Methods: We designed and piloted a System-Oriented Dialogue Model with the participation of 44 teachers and 868 students and their parents from six Spanish schools during 2021. The results were analysed using thematic analysis.Results: Participants identified 406 items addressing issues related to system characteristics, which is indicative of the complexity of the challenge. Using a thematic analysis, we defined 14 recommendations covering five categories.Conclusion: These findings could help in developing guidelines for initiating community engagement partnerships in schools to provide more integrated prevention interventions.